Interaction of Two-Level Atom with Squeezed Vacuum Reservoir - Tamirat Abebe; Demissie Jobir; Chimdessa Gashu; Ebisa Mosisa (Advances in Mathematical Physics)
In this paper, the quantum properties of a two-level atom interaction with squeezed vacuum reservoir is throughly analyzed. With the aid of the interaction Hamiltonian and the master equation, we obtain the time evolution of the expectation values of the atomic operators. Employing the steady-state solution of these equations, we calculate the power spectrum and the second-order correlation function for the interaction of two-level atom with squeezed vacuum reservoir. It is found that the half width of the power spectrum of the light increases with the squeeze parameter, r. Furthermore, in the absence of decay constant and interaction time, it enhances the probability for the atom to be in the upper level.